1984
DOI: 10.1038/icb.1984.64
|View full text |Cite
|
Sign up to set email alerts
|

The Respiration and Energy Metabolism of Sheep Lymphocytes

Abstract: Summary The respiration characteristics and energy metabolism of sheep lymphocytes collected from the popliteal lymph before and after antigenic challenge with Salmonella organisms have been studied at various O2 tensions. The O2 consumption of sheep lymphocytes could be related to the PO2 of the medium by the Michaelis‐Menten equation. In resting lymphocytes, Vmax (mean ± S.D.) was 1·70 ± 0·23 μmoles/h/2 × 108 cells), critical O2 concentration ([O2]crit) was 2·00 ± 0·20 μM and Km was 0·46 ± 0·11 μM. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…A critical oxygen concentration of 0.02 mmolil has been observed for the present cell line (Backman and Wadso, 1991). This is in agreement with critical oxygen concentrations observed for, e.g., hepatocytes (0.01-0.02 mmolil), (Jones and Mason, 1978) and sheep lymphocytes (0.0002-0.02 mmolil), (Cheung and Morris, 1984). Apparent Michaelis-Menten constants for intact cells (e.g., Jones and Mason, 1978) are typically 10 times higher than for isolated mitochondria (Jones and Mason, 1978;Cole et al, 1982;Sugano et al, 1974) which is explained by intracellular diffusion gradients, presumably due to clustering of mitochondria (Jones, 1986).…”
Section: Discussionsupporting
confidence: 91%
“…A critical oxygen concentration of 0.02 mmolil has been observed for the present cell line (Backman and Wadso, 1991). This is in agreement with critical oxygen concentrations observed for, e.g., hepatocytes (0.01-0.02 mmolil), (Jones and Mason, 1978) and sheep lymphocytes (0.0002-0.02 mmolil), (Cheung and Morris, 1984). Apparent Michaelis-Menten constants for intact cells (e.g., Jones and Mason, 1978) are typically 10 times higher than for isolated mitochondria (Jones and Mason, 1978;Cole et al, 1982;Sugano et al, 1974) which is explained by intracellular diffusion gradients, presumably due to clustering of mitochondria (Jones, 1986).…”
Section: Discussionsupporting
confidence: 91%
“…Metabolic requirements of leucocytes also increase when these cells are activated. Oxygen consumption, glucose utilization and glutamine utilization increase two‐ to threefold on a per cell basis (21,22). However, fever may not be a prominent feature of most GIN infections.…”
Section: Potential Costs Of Host Responses To Gastrointestinal Nematomentioning
confidence: 99%
“…Results Oxygen consumption and lactate production rates as a function of concentration were highly nonlinear and appeared to follow Michaelis-Menten kinetics, with rates falling steeply with fall in concentration as seen for other tissues (Cheung & Morris 1984). We confirmed that the chondrocytes demonstrated a negative Pasteur effect (Lee & Urban 1997) (i.e., inhibition of glycolysis under low oxygen) and a Crabtree effect (stimulation of oxygen consumption under low glucose) (Otte 1991), as described by others previously.…”
Section: Measurements Of Metabolic Rates For Cartilage Tissue-engineementioning
confidence: 79%